Implementing surgical services in a rural, resource-limited setting: a study protocol. Issue 1 (4th August 2011) - Maru, Duncan Smith-Rohrberg; Schwarz, Ryan; Schwarz, Dan; Andrews, Jason; Panizales, Maria Theresa; Karelas, Gregory; Brady, Jesse Stark; Rogers, Selwyn
Abstract : Introduction: There are well-established protocols and procedures for the majority of common surgical diseases, yet surgical services remain largely inaccessible for much of the world's rural poor. Data on the process and outcome of surgical care expansion, however, are very limited, and the roll-out process of rural surgical implementation in particular has never been studied. Here, we propose the first implementation research study to assess the surgical scale-up process in the rural district of Achham, Nepal. Methods and analysis: Based primarily on the protocols of the WHO's Integrated Management for Emergency and Essential Surgical Care (IMEESC), this study's threefold implementation strategy will include: (1) the core IMEESC surgical care program, (2) community-based follow-up via health workers, and (3) hospital-based quality improvement programs. The implementation program will employ additional emergency and surgical care protocols developed collaboratively by physicians, nurses and the authors. This strategy will be referred to as IMEESC-Plus. This study will employ both qualitative and quantitative research methodologies to collect clinical data and information on the reception and utilisation of services. The first 18 months of the implementation process will be studied and divided into an initial phase (first 6 months) and a consolidation phase (subsequent 12 months). Discussion: This study aims to describe the logistics of the implementation process of IMEESC-Plus, and assess the quality of the resulting IMEESC-Plus services during the course of the implementation process. Using data generated from this study, larger, multi-site implementation studies can be planned that assess the scale-up of surgical services worldwide in resource-limited areas.